Les stratégies rédactionnelles face aux défis d’interprétation d’un débat radiodiffusé - Wojciechowska, Bernadeta; Górecka, Joanna; Richard, Elisabeth; Le Bot, Marie-Claire (Studia Romanica Posnaniensia, 2014)
The research presented in the paper is a part of the project carried out at the Institute of Romance Languages and Literatures at the University of Adam Mickiewicz in Poznań. The research aims at determining the underdeveloped areas of advanced learners’ listening skills. The ultimate objective of our research is the development of discursive approach toward teaching and learning (Górecka, Wilczyńska, Wojciechowska in press). The study focuses on analyzing writing strategies used by students in the task of summarizing the chosen sequences of media debates in the radio program Le téléphone sonne. We claim that the way the students formulate their answers can reveal, to some extent, the diffi culties they encounter in analyzing and synthetizing oral discourse. The analysis of students’ writing strategies may contribute to the elaboration of pre-task instructions and evaluation techniques, which may result in a better approach to the development of listening skills.